A Social Priming Data Set With Troubling Oddities. Issue 1 (2nd January 2016) - Pashler, Harold; Rohrer, Doug; Abramson, Ian; Wolfson, Tanya; Harris, Christine R.
ABSTRACT: A recent paper by Chatterjee, Rose, and Sinha (2013) reported impressively large "money priming" effects: incidental exposure to concepts relating to cash or credit cards made participants much less generous with their time and money (after cash primes) or much more generous (after credit card primes ). Primes also altered participants' choices in a word-stem completion task. To explore these effects, we carried out re-analyses of the raw data. A number of strange oddities were brought to light, including a dramatic similarity of the filler word-stem completion responses produced by the 20 subjects who contributed most to the priming effects. We suggest that these oddities undermine the credibility of the paper and require further investigation.